Fruit fly infestation of cucurbitaceous vegetables in Morogoro—Eastern Central Tanzania - Petronila Tarimo; Sija Kabota; Ramadhan Majubwa; Abdul Kudra; Massimiliano Virgilio; Kurt Jordaens; Marc De Meyer; Maulid Mwatawala (PLoS ONE, 2025)
Fruit flies (Diptera: Tephritidae) are a significant threat to cucurbit production in Tanzania. To effectively combat these pests, it is crucial to understand the patterns of fruit fly infestations among cucurbit crops at different altitudes. Our study focused on the infestation patterns of fruit flies among commonly grown cucurbit crops—cucumber (Cucumis sativus L.), watermelon (Citrullus lanatus [Thunb.] Matsum. & Nakai), and squash (Cucurbita moschata D.) in Eastern Central Tanzania. The research was conducted in the “plateau” (low altitude) and the “mountainous” (high altitude) areas of Morogoro over three cropping seasons (March - April as Season I, June – July as Season II, and September – October as Season III) during 2020. We collected a total of 450 samples equivalent to 4,500 fruits during this period. Out of these, 418 samples were infested by five fruit fly species: Zeugodacus cucurbitae (Coquillett), Dacus ciliatus Loew, Dacus vertebratus Bezzi, Dacus bivittatus (Bigot), and Dacus punctatifrons Karsch, which are the principal tephritid pests of cucurbit crops in Morogoro. In total, 22,169 fruit flies were recovered from the samples, with more flies emerging from the mountainous zone (12,390) than the plateau (9,779). Zeugodacus cucurbitae accounted for the majority of the emerged flies (18,789), while the remaining species, including D. vertebratus and D. ciliatus, contributed smaller numbers. Among the hosts, Cucumis sativus was the most heavily infested, followed by Cucurbit moschata and Citrullus lanatus. Significant effects of fruit fly species × host species and fruit fly species × agroecological zone on percent infestation and degree of infestation. Furthermore, the effects of host species × agroecological zone on percent infestation were significant. The study further found that that Z. cucurbitae was the dominant pest in terms of percent and degree of infestation among the three cucurbit crops at both agroecological zones in the Morogoro region. These findings provide valuable insights into severity of pest infestation that may cause high economic losses in cucurbit crops in cucurbit production. The study recommends that any management strategies for fruit flies should focus on controlling Z. cucurbitae, as a key pest of cucurbits in the region.